Stoma complications before and after the introduction of stoma siting performed by nurses: a retrospective study (Dissertation Nursing, 2022)
BACKGROUND: 3%-82% of stoma patients suffer from ostomy complications, which determine an increased assistance burden with the lengthening of the hospital stay and of the time needed to recover the autonomy of the stoma. Literature shows that the lack of a preoperative stoma design is one of the factors increasing the bearing of ostomy complications, along with the urgency of the operation, the height and type of the stoma, and body mass index.AIM: Evaluating the number and characteristics of ostomy complications in the period before the introduction of the preoperative ostomy design procedure (i.e. stoma siting) performed by the nurse. Comparing these numbers with those concerning complications detected in the period after the introduction of the stoma siting procedure.METHODS: Monocentric retrospective observational study, in the operating units of General Surgery and Urology of San Paolo hospital of ASST Santi Paolo e Carlo, Milan. Convenience samples of patients undergoing enteral and urinary ostomy. RESULTS: 264 patients were recruited. 51.1% had experienced ostomy complications; 42.9% of them had undergone stoma siting, 61.5% had not. The most frequent complications were peristomal skin changes (29.9%). The difference in numbers between the individual types of complications in the two groups is clinically relevant.CONCLUSIONS: Stoma siting is a nursing procedure that, if well performed, leads to the reduction of ostomy complications. It is the nurse’s responsibility to ensure each patient who undergoes ostomy packing the correct execution of the ostomy design – whenever the conditions of the clinical picture allow it.
Keywords: stoma siting; complications; nurse; stomatherapist; stomatherapy